INCLUSIVE EDUCATION AND SECTORAL COLLABORATION: A LITERATURE ANALYSIS OF CHALLENGES AND OPPORTUNITIES - Novianty Djafri; Mujahidin (CV. ADIBA AISHA AMIRA, 2025)
This research analyses the challenges and opportunities in implementing inclusive education through sectoral collaboration. Inclusive education aims to provide a learning environment that can accommodate a diverse range of students, including those with special needs. However, there are a number of challenges that need to be overcome to realise this goal, such as limited resources, lack of teacher training and structural and policy barriers. Through a literature review, this research highlights the importance of collaboration between different sectors, including government, schools, non- governmental organisations and communities, to overcome these challenges. Sectoral collaboration can provide the necessary resources, improve teacher competencies and create policies that support inclusive education. The research also identifies opportunities that can be optimised through a collaborative approach, ultimately creating a more inclusive, equitable and quality education system for all students